Essential oils as an effective alternative for the treatment of COVID-19: Molecular interaction analysis of protease (Mpro) with pharmacokinetics and toxicological properties - Sukanya Panikar; Gunasekaran Shoba; Muthukrishnan Arun; Jesudass Joseph Sahayarayan; A. Usha Raja Nanthini; Arunachalam Chinnathambi; Sulaiman A. Alharbi; Omaima Nasif; Hak-Jae Kim (Elsevier, 2021)
Background: The current health concern to the entire world is the chronic respiratory disease caused by coronavirus 2 (COVID-19). A specific treatment or proper therapy is still lacking, and the investigations from across the world for proper drug/vaccine development towards disease control are in progress. The Coronavirus replication takes place by the conversion of the polypeptide into functional protein and this occurs due to the key enzyme Main protease (Mpro). Therefore, identification of natural and effective Mpro inhibitors could be a safe and promising approach for COVID-19 control. Methods: The present in silico study evaluates the effect of bioactive compounds found in Eucalyptus and Corymbia species essential oil on Mpro by docking. Molecular docking of the major seven compounds of essential oil (citronellol, alpha-terpineol, eucalyptol, d-limonene, 3-carene, o-cymene, and alpha-pinene) with Mpro was studied by AutoDock 4.2, and the properties were analysed by PreADMET and Biovia Discovery Studio visualizer. Results: The calculated parameters such as binding energy, hydrophobic interactions, and hydrogen bond interactions of 6LU7 (Mpro) with Eucalyptus and Corymbia volatile secondary metabolites represented its scope as an effective therapy option against covid-19. Among the docked compounds, eucalyptol shows the least binding energy without toxicity. Conclusions: The outcome of this study reported that the essential oil of Eucalyptus and Corymbia species, mainly eucalyptol can be utilized as a potential inhibitor against COVID-19 and also it can be used in its treatment. Hence, further analysis was required to explore its potential application in medicine.